Automated assays for von Willebrand factor activity. Issue 4 (10th January 2019) - Higgins, Russell A.; Goodwin, Andrew J.
Abstract : von Willebrand factor (VWF) ristocetin cofactor activity (VWF:RCo) by platelet aggregometry has been considered the gold standard for evaluating the ability of VWF to bind platelets for over 40 years. Many automated systems no longer require platelets and rather rely on agglutination of latex particles. Automated methods of measuring VWF activity have improved performance characteristics and are performed on the same coagulation instruments used for routine testing via immunoturbidimetric methodology. Alternatively, a newer chemiluminescence assay system for measuring VWF activity demonstrates excellent performance characteristics. As these methods are becoming widely used, it is important to assess their performance in diagnosing and monitoring different types of von Willebrand disease. We review the automated methodologies and the published performance of these VWF assays. Advantages and limitations of these automated methods are discussed.